Pemikiran Pendidikan Islam Zakiah Daradjat: Analisis Kritis dan Relevansinya bagi PAI Kontemporer - Fitria Faradina Kafa Aula Kafa Aula; Siti Fatimah; Putri Firdaus Fahmi; Khafidoh Khafidoh; Mulyanto Abdullah Khoir (LaKaspia, 2025)
Islamic education aims at the holistic development of learners, encompassing cognitive, affective, and psychomotor dimensions, as well as the cultivation of faith, morality, and mental health. Zakiah Daradjat is a prominent Indonesian Islamic education scholar who introduced an integrative approach between Islamic education and the psychology of religion, particularly within the context of Islamic Religious Education (Pendidikan Agama Islam/PAI). However, previous studies on her thought have largely remained descriptive and have not sufficiently engaged in critical analysis in relation to contemporary educational challenges. This study aims to critically analyze Zakiah Daradjat’s Islamic educational thought by examining its contributions, conceptual uniqueness, and relevance to the development of contemporary Islamic Religious Education in Indonesia. Employing a qualitative approach through library research, the study utilizes Daradjat’s original works as primary sources and relevant academic literature as secondary sources. Data analysis is conducted using content analysis with an emphasis on thematic and critical interpretation. The findings indicate that Zakiah Daradjat’s educational thought emphasizes a holistic, integrative, and contextual model of Islamic education grounded in the Qur’an, Sunnah, and ijtihad, and implemented synergistically across family, school, and community settings. The integration of Islamic education and the psychology of religion represents her distinctive contribution, particularly in strengthening learners’ character formation and mental health. Nevertheless, her ideas require deeper engagement with contemporary educational theories and pedagogical approaches to remain adaptive to global and digital challenges. Theoretically and practically, Zakiah Daradjat’s Islamic educational thought remains relevant as a foundation for the development of modern Islamic Religious Education, especially in addressing moral degradation and students’ mental health issues in Indonesia.